Developing Mathematic Learning Devices Oriented Problem Based Learning to improve Students' High Order Thinking Skill - Qohar, Moh. Abdul; Susanti, Nawal Ika; Wahyu, Rahma (Jurnal Pendidikan Matematika, 2025)
Students demonstrate low proficiency in answering HOTS (Higher Order Thinking Skills) questions, indicating the need for a learning model that aligns with the nature and demands of such questions. One such suitable model is Problem-Based Learning (PBL), which serves as a relevant and applicable approach for the current curriculum. This study aims to develop a mathematics learning tool based on the Problem-Based Learning (PBL) model to enhance students’ higher-order thinking skills (HOTS). This research employed the 4D Model in the research and development (R&D) approach, encompassing the stage of define, design, develop, and dissemination. The sampling used a purposive sampling technique, namely 22 students of SMP Plus Darussalam Blokagung Banyuwangi. The expert validation results showed that the lesson plan (RPP) achieved an average score of 92.2%, placing it in the "highly valid" category. The learning tool's practicality earned an average of 95.4% (very practical), whereas the student worksheet's (LKS) validation yielded 90.4% (extremely viable). During the dissemination stage, the effectiveness was measured using the N-Gain method. Data were collected through test designs to measure HOTS. Using essay questions in pre-test and post-test that focused on the HOTS indicators: analysis, evaluation, and creation. The results indicated a significant improvement in students' HOTS with an average score of 0.915a (High category) for analysis, 0.675 (medium category) for evaluation, and 0.54 (low category) for creation. These findings indicated that the problem-based learning tool effectively enhances students' higher-order thinking skills (HOTS). Kemampuan siswa dalam menyelesaiakan soal soal HOTS masih sangat rendah sehingga dibutuhkan model pembelajaran yang sesuai dengan ciri ciri soal HOTS. Salah satunya adalah model pembelajaran PBL mampu menjadi pendekatan yang relevan dan aplikatif untuk kurikulum saat ini. Penelitian ini bertujuan untuk mengembangan Perangkat pembelajaran Matematika model Problem-Based Learning (PBL) dalam meningkatkan keterampilan berpikir tingkat tinggi (HOTS). Penelitian ini menggunakan Model 4D dalam pendekatan penelitian dan pengembangan (R&D) yang mencakup define, design, develop, and dissemination. Pengambilan sampel menggunakan teknik purposif sampling yaitu 22 siswa SMP Plus Darussalam Blokagung Banyuwangi. Hasil Validasi oleh Ahli memperoleh rata-rata RPP 92,2% (kategori sangat Valid), dan validasi LKS memperoleh 90,4% (Kategori sangat layak), sedangkan dalam kepraktisan perangkat mendapatkan ra-rata 95,4% (kategori sangat praktis). Pada tahap dessiminasi untuk mengukur keefektifitasnya menggunakan metode N-Gain. Data dikumpulkan menggunakan tes yang mengukur HOTS. Menggunakan soal esai dalam pre-test dan post-test, indikator HOTS—analisis, evaluasi, dan kreasi. Menghasilkan peningkatan yang signifikan dalam HOTS siswa dengan skor rata-rata 0,915 (menganalisis) kategori tinggi, 0,675 (mengevaluasi) kategori menengah, dan 0,54 (mengkreasi) kategori rendah, sehingga menunjukkan bahwa perangkat pembelajaran berbasis problem based learning yang dihasilkan secara efektif meningkatkan kemampuan berfikir tingkat tinggi siswa (HOTS).